2014
DOI: 10.3390/f5030518
|View full text |Cite
|
Sign up to set email alerts
|

Process-Based Modeling to Assess the Effects of Recent Climatic Variation on Site Productivity and Forest Function across Western North America

Abstract: A process-based forest growth model, 3-PG (Physiological Principles Predicting Growth), parameterized with values of soil properties constrained by satellite-derived estimates of maximum leaf area index (LAI max ), was run for Douglas-fir (Pseudotsuga menziesii) to contrast the extent to which site growth potential might vary across western North America between a cool, wet period and a more recent, generally warmer and drier one (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009). LAI max represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
0
13
0
5
Order By: Relevance
“…Most authors agree that observed age trend in site index estimates are the result of changing site conditions (Nothdurft et al 2012, Pretzsch et al 2012, Waring et al 2014, Yue et al 2014. However, in this paper more localized site index models developed for the Carpathians did not revealed correlations with the age of stands.…”
Section: Discussionmentioning
confidence: 44%
“…Most authors agree that observed age trend in site index estimates are the result of changing site conditions (Nothdurft et al 2012, Pretzsch et al 2012, Waring et al 2014, Yue et al 2014. However, in this paper more localized site index models developed for the Carpathians did not revealed correlations with the age of stands.…”
Section: Discussionmentioning
confidence: 44%
“…In western coniferous forests, LAI varies from < 1 to 12 m 2 ?m −2 (Runyon et al 1994;Waring et al 2014). If growing conditions become less favorable, the LAI will decrease, often abruptly (Pook 1984), which can result in increased tree mortality.…”
Section: Approachmentioning
confidence: 99%
“…The soil receives a fraction of the precipitation for each month, and the soil water that is not released through evapotranspiration is added to the next month? s water balance or allowed to run off (Landsberg and Waring 1997;Waring et al 2014). ASW is defined as the difference between field capacity (soil moisture held at 1/3 bar tension) and wilting point (soil moisture held at 15 bar tension).…”
Section: -Pg Process Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In process-based models, carbon sequestration is computed from empirically derived relationships between physiological parameters such as photosynthesis, and environmental factors such as atmospheric and growing condition variables (Waring et al 2014). By responding to external control factors, process-based models inform how changes in environmental conditions may mechanistically influence changes in forest carbon stocks and fluxes.…”
Section: Metrics Of Forest Carbon Fluxesmentioning
confidence: 99%